Distribution of Clay Minerals in Tambunan A Field Experimental of University of Sumatera Utara at Salapian Sub-district of Langkat Regency - Louis Manihuruk; Purba Marpaung; Alida Lubis (Jurnal Agroekoteknologi, 2019)
Distribution of Clay Mineral in Tambunan A Field Experimental of University of Sumatera Utara at Salapian Sub-district of Langkat Regency. This research was conducted in Tambunan A Field Experimental of University of Sumatera Utara at Salapian Sub-district, Langkat Regency. Laboratory analysis was conducted at PT. Socfindo Medan and Educational Laboratory of Industrial Chemical Technology Medan. The study was conducted from March 2017 until October 2017. The analysis of clay minerals using Differential Thermal Analysis (DTA) tools on 5 soil profiles determined by slopes. The result showed that the profile I had 4 horizon layers of Ap1, Ap2, Ap3, and Bw horizon, Profile II had 6 horizon layers Ap1, Ap2, Bw1, Bw2, Bw3, and BC, Profile III had 5 horizon layers ie Ap1, Ap2, Ap3, Bw1, and Bw2, Profile IV had 5 horizon layers of Ap, Apw, Bw1, Bw2, and Bw3 and Profile V had 6 horizon layers Ap1, Ap2, Ap3, Bw1, Bw2, and Bw3. DTA analysis results showed that the clay mineral species contained were allophane-a, and kaolinite. Alofan-a and kaolinite were present in all horizon layers in all profiles whereas gibsit are not present on all layers of soil horizon.Keywords : Differential Thermal Analysis, Tambunan A, Langkat Regency